Avaliação de líquidos iônicos para aplicações em células fotovoltaicas - Ribas, Caroline dos Santos (2018)
The present study deals with an evaluation of ionic liquids for applications in photovoltaic cells. Among the photovoltaic cells there are the so-called dye sensitized sollar cells that basically work by a oxireduction reaction of the dye. The dye is restrained in a solvent and due to the difficult encapsulation of volatile solvents it is one of the main problems making these cells not efficient. These cells are not yet part of the market, however, because they have many advantages compared to other cells, many researchers have been studying these devices, mainly in search of compounds that replace these volatile solvents. Ionic liquids are organic compounds formed by one or more cations and one or more anions with intrinsic properties such as non-volatility, non-flammability, high ionic conductivity and thermal stability and therefore they are very promising to replace the volatile solvents. The aim of this work was to select ionic liquids, to make the synthesis and then to analyze the impedance in the pure state and in solution and to identify their viscosity. The selected ionic liquids were the 2-(3-methylimidazolyl-1-yl)etoxy-4-oxobutanoico acid bromide (Ionic Liquid of Succinic Anhydride) and the 2-(3-methylimidazolyl-1-yl)-etoxy-carbonyl-benzoic-phthalic acid bromide, because they presented better yields. The impedance analysis was performed using the Impedance Spectroscopy technique which showed the briefly behavior of these compounds and revealed a higher stability when they are in aqueous solution. As for viscosity, it was initially proposed to perform the rheology of the samples, but soon it was verified that the time required for each analysis would extrapolate the time that was available for the accomplishment of this work. The viscosity analysis was then attempted by physical-chemical laboratories, but this was not possible due to the large volume of sample required.